New Mana: Transformations of a Classic Concept in Pacific Languages and Cultures - Matt Tomlinson (ANU Press, 2016)
'Mana', a term denoting spiritual power, is found in many Pacific Islands languages. In recent decades, the term has been taken up in New Age movements and online fantasy gaming. In this book, 16 contributors examine mana through ethnographic, linguistic, and historical lenses to understand its transformations in past and present. The authors consider a range of contexts including Indigenous sovereignty movements, Christian missions and Bible translations, the commodification of cultural heritage, and the dynamics of diaspora. Their investigations move across diverse island groups-Papua New Guinea, Solomon Islands, Vanuatu, Fiji, Tonga, Samoa, Hawai'i, and French Polynesia-and into Australia, North America and even cyberspace. A key insight that the volume develops is that mana can be analysed most productively by paying close attention to its ethical and aesthetic dimensions. Since the late nineteenth century, mana has been an object of intense scholarly interest. Writers in many fields including anthropology, linguistics, history, religion, philosophy, and missiology have long debated how the term should best be understood. The authors in this volume review mana's complex intellectual history but also describe the remarkable transformations going on in the present day as scholars, activists, church leaders, artists, and entrepreneurs take up mana in new ways.